The Challenges of Digital Competency Implementation Towards World-Class Bureaucracy - Cahyarini, Benedicta Retna; Samsara, Ladiatno (Pusjar SKPP Lembaga Administrasi Negara, 2021)
Industrial revolution 4.0 creates various improvements toward technology utilisation in every sector, offering efficiencies in every part of life. As a consequence, the government needs to respond to it in public service practices. Therefore, digital competency is mandatory for Indonesian civil servants. Due to the lack of civil servant's competency in technology usage and the bureaucratic environment, the Indonesian government sees this as a big challenge. Moreover, digital competency improvement must be carried out from both training and development in terms of competency development. Thus, using a qualitative descriptive method with a desk study review from various literature sources, such as books and news (printed and online), this paper offers an overview of the challenges and solutions in implementing digital competency in the public sector, both internally and externally. Internally, the technology utilisation solutions are focused on technology infrastructure improvement, strengthening civil servant's competencies, work habit transformation, and organisational relations. On the other hand, from the external side, the solution comes from the contract-based government employee’s (PPPK) recruitment and collaboration with the private sector, as often done by many government agencies. However, whatever solution is chosen, strengthening the usage of information technology in the public sector will always face challenges.